The Agronomic and Quality Descriptions of Ethiopian Bread wheat (Triticum aestivum L.) Variety “Boru” - Alemu, Gadisa; Geleta, Negash; Dabi, Alemu; Duga, Ruth; Kasahun, Cherinet; Delasa, Abebe; Negash, Tamirat; Solomon, Tafesse; Zegaye, Habtemariam; Getamesay, Abebe; Asnake, Dawit; Asefa, Bayisa; et al. (International Journal of Bio-resource and Stress Management, 2022)
A multiplications evaluation was conducted with twenty-eight advanced bread wheat genotypes and two standard checks for two consecutive years 2017 and 2018 at Kulumsa, Asasa, Robe Arsi, Bekoji, Areka, Shambu, Holeta, Adet, Enawari, Awalgera, and Debra Zeit, Ethiopia. The objective of the paper was to describe the agronomic and quality related traits of newly developed bread wheat varieties “Boru” for optimum moisture areas of Ethiopia. Boru is a commercial name given for a newly released variety with the pedigree name SAUAL/MUTUS/6/CNO79//PF70354/MUS/3/PASTOR/4/BAV92*2/5/FH6-1-7/7/CNO79//PF. 70354/MUS/3/PASTOR/4/BAV92*2/5/FH6-1-7 which originated from CIMMYT germplasms. Boru is adapted within the range of altitude 2050 to 2780 masl with annual rainfall amount receiving from 620 to 1290 mm. Boru showed superior overall agronomic performances over the standard check Wane and Hidasse and it had a 9% and 14% yield advantage respectively. The new variety had a bold seed size than the two checks. Boru variety showed relative resistance to stem, yellow and leaf rust as compared to wheat varieties under production at the medium to high land wheat-growing agro-ecologies. Boru offers new hope for resource-poor farmers in rust-prone areas of Ethiopia. It’s expected to replace the variety ‘Ogolcho’ in medium areas, and ‘Hidasse’ in high land areas of Ethiopia. In addition, the Boru variety is known for its higher protein content (14.37%) than standard check Wane (12.14%) and local check Hidasse (12.3%).